A Portrait of Learner’s Autonomy through Metacognitive Strategy on Reading Comprehension (A Study At SMP N 32 Semarang) - Kartika Ayu Septiningrum; Siti Tarwiyah; Siti Mariam (Universitas Islam Negeri Walisongo Semarang, 2018)
Autonomy or the capacity to take charge of one's learning is seen not only as a favorite topic but also as a crucial necessity in language learning.In Indonesia, the principle of autonomous learning was implemented in the 2013 curriculum. This research aimed to capture the practice of learner autonomy and its role in the learning process through a strategy which is used in practicing autonomy. Metacognitive strategy, which has a planning process, monitoring process, problem-solving process, and evaluating process is necessary for learners' autonomy. The qualitative research method was used in conducting this research. Three data collection methods were used in capturing the data in all metacognitive's process. Each method has its dimension in collecting the data. A participatory observation was used to collect data from activeness dimension. A student questionnaire was used to find out awareness dimension while an interview was used for responsibility and ability dimensions. The data from these data collection methods were triangulated. This research has the flexibility to be conducted in any institution where the 2013 curriculum is implemented. SMP N 32 Semarang was chosen for this reason. Based on the research, the learners are autonomous, they are active, aware, responsible, and able to take control of their learning in all metacognitive strategy processes (planning, monitoring, problem-solving and evaluating), yet they are not completely free from teacher’s guidance, they need it in making a plan, monitoring, solving problem, and evaluating their learning.